2016
DOI: 10.1038/srep19916
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated expression of IDO may cause unexplained recurrent spontaneous abortion through suppression of trophoblast cell proliferation and migration

Abstract: In pregnancy, trophoblast proliferation, migration and invasion are important for the establishment and maintenance of a successful pregnancy. Impaired trophoblast function has been implicated in recurrent spontaneous abortion (RSA), a major complication of pregnancy, but the underlying mechanisms remain unclear. Indoleamine 2,3-dioxygenase (IDO), an enzyme that catabolizes tryptophan along the kynurenine pathway, is highly expressed in the placenta and serum during pregnancy. Here, we identified a novel funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 36 publications
4
60
0
Order By: Relevance
“…4e). Moreover, our previous researches have demonstrated that overexpression of STAT3 obviously improved the migration of HTR-8/SVneo trophoblast cells [24]. These results above suggest that STAT3, or signaling events upstream of STAT3, might be targeted by THC in vitro .…”
Section: Resultsmentioning
confidence: 65%
“…4e). Moreover, our previous researches have demonstrated that overexpression of STAT3 obviously improved the migration of HTR-8/SVneo trophoblast cells [24]. These results above suggest that STAT3, or signaling events upstream of STAT3, might be targeted by THC in vitro .…”
Section: Resultsmentioning
confidence: 65%
“…Reduced IDO expression and attenuated Trp catabolism in placenta were detected in the PE group [ 135 , 144 ]. The IDO expression in endothelial cells was down-regulated in PE placentas, which might be related to shallow placentation, an incentive of PE [ 145 , 146 , 147 ]. In addition, decreased IDO expression was found to be associated with the severity of PE, containing severe maternal hypertension and proteinuria, dysregulation of the inflammatory response [ 134 , 135 ].…”
Section: Trp Metabolism In Abnormal Pregnanciesmentioning
confidence: 99%
“…Recurrent miscarriage (RM), defined as at least two consecutive spontaneous pregnancy losses before 20 weeks gestation, affects up to 5% of women around the world. Some known factors, including infection, chromosomal abnormalities and uterine abnormalities, were proven to cause RM, but approximate 50% cases were unexplained [ 145 ]. Immunological dysfunction and OS were suggested to be the cause of the unexplained proportion [ 146 , 153 ].…”
Section: Trp Metabolism In Abnormal Pregnanciesmentioning
confidence: 99%
“…Recurrent spontaneous abortion (RSA) refers to two or more consecutive miscarriages before 20 weeks gestation with the same partner (Zong et al, ). It is estimated that RSA affects approximately 1–5% women at the reproductive age around the world (Zong et al, ). The etiology of RSA is extremely complex (Rai and Regan, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that trophoblast cells are essential to both placental and fetal development (Pollheimer et al, 2006). Defects in trophoblast cell function have been associated with pregnancy-related complications such as URSA, intrauterine growth retardation, and pre-eclampsia (Ferreira et al, 2011;Pennington et al, 2012;Zong et al, 2016). Recent evidence suggested that Wingless (Wnt) signaling is critical for physiological processes of human trophoblasts and might be involved in the pathogenesis of URSA (Knofler and Pollheimer, 2013;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%